2015
DOI: 10.1007/s10753-015-0189-y
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptor Expression in Peripheral Blood Monocytes Is Correlated With Plasma C-Reactive Protein and Cytokine Levels in Patients With Type 2 Diabetes Mellitus: a Preliminary Report

Abstract: Chronic inflammation plays a major role in development of type 2 diabetes mellitus (T2DM). C-reactive protein (CRP) and inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin 1β (IL-1β) are directly involved in the occurrence of insulin resistance. Increased extracellular ATP levels can amplify the inflammatory response in vivo via the P2X7 receptor. The present study aimed to assess the relationship between P2X7 receptor expression in human peripheral blood monocytes and plasma levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Previous studies suggested that IL-10 could suppress the proliferation of T leukomonocyte and the secretion of cytokines [ 121 ], whereas TGF- β may sustain the expression of Foxp3 in CD4 + CD25 + Treg to enhance immunosuppressive function [ 122 , 123 ]. Consistent with our findings, several studies have shown a significantly decreased level of serum IL-10 in T2DM patients [ 88 , 124 ]. Correlation of T2DM with Treg cells and TGF- β is generally negative [ 116 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies suggested that IL-10 could suppress the proliferation of T leukomonocyte and the secretion of cytokines [ 121 ], whereas TGF- β may sustain the expression of Foxp3 in CD4 + CD25 + Treg to enhance immunosuppressive function [ 122 , 123 ]. Consistent with our findings, several studies have shown a significantly decreased level of serum IL-10 in T2DM patients [ 88 , 124 ]. Correlation of T2DM with Treg cells and TGF- β is generally negative [ 116 ].…”
Section: Discussionsupporting
confidence: 93%
“…The experiments in the present study showed that the mRNA and protein expression of P2X 7 R in RAW264.7 cells were increased due to high glucose and high FFA treatment, compared with those in the controls. This was similar to the results of our preliminary investigation (6,27), which showed that the P2X 7 R may alter the innate immune system contributing to the development of T2DM. The present study was limited by the fact that no binding assays were performed to examine the binding of ATP to P2X 7 R. Future investigations aim to improve on this aspect of the pilot study.…”
Section: Discussionsupporting
confidence: 91%
“…The events leading to T2dM are complex, however, emerging evidence has shown that various purinergic signaling components may be important regulatory factors (20,21). Our previous preliminary study demonstrated that P2X 7 R in peripheral blood monocytes may be involved in the pathological changes of T2dM, particularly affecting patients with high CRP levels (6). In the previous study, it was found that the expression of uc.48+ in the serum of patients with T2DM and in RAW264.7 macrophages treated with high glucose and high FFAs was significantly increased, compared with the expression in the healthy individuals and control group, respectively.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…P2X7 receptors on monocytes may be involved in the pathological changes of type 2 diabetes mellitus, particularly in patients with high C-reactive protein levels. 204 Up 4 A is a vessel constrictor and is associated with diabetes mellitus. 205 Adenosine-insulin signaling in fetoplacental endothelial dysfunction in gestational diabetes mellitus has been reviewed.…”
Section: Diabetic Vascular Diseasementioning
confidence: 99%